Measurements of Argon-39 at the U20az underground nuclear explosion site. (November 2017) - McIntyre, J.I.; Aalseth, C.E.; Alexander, T.R.; Back, H.O.; Bellgraph, B.J.; Bowyer, T.W.; Chipman, V.; Cooper, M.W.; Day, A.R.; Drellack, S.; Foxe, M.P.; Fritz, B.G.; et al.
Abstract: Pacific Northwest National Laboratory reports on the detection of 39 Ar at the location of an underground nuclear explosion on the Nevada Nuclear Security Site. The presence of 39 Ar was not anticipated at the outset of the experimental campaign but results from this work demonstrated that it is present, along with 37 Ar and 85 Kr in the subsurface at the site of an underground nuclear explosion. Our analysis showed that by using state-of-the-art technology optimized for radioargon measurements, it was difficult to distinguish 39 Ar from the fission product 85 Kr. Proportional counters are currently used for high-sensitivity measurement of 37 Ar and 39 Ar. Physical and chemical separation processes are used to separate argon from air or soil gas, yielding pure argon with contaminant gases reduced to the parts-per-million level or below. However, even with purification at these levels, the beta decay signature of 85 Kr can be mistaken for that of 39 Ar, and the presence of either isotope increases the measurement background level for the measurement of 37 Ar. Measured values for the 39 Ar measured at the site ranged from 36, 000 milli- Becquerel/standard-cubic-meter-of-air (mBq/SCM) for shallow bore holes to 997, 000 mBq/SCM from the rubble chimney from the underground nuclear explosion. Highlights: We report on the detection of 39 Ar at the location of an underground nuclear explosion on the Nevada Nuclear Security Site. Argon-39 was detected, along with 37 Ar and 85 Kr in the subsurface at the Barnwell underground nuclear explosion. These isotopes are produced through fission ( 85 Kr) through the 40 Ca( n, alpha ) 37 Ar reaction or 39 K( n, p ) 39 Ar reaction. Measured values for the 39 Ar ranged from 36, 000 (mBq/SCM) for shallow bore holes to 997, 000 mBq/SCM from the rubble chimney. Argon-39 and 85 Kr, could interfere with gas sampling and detection equipment used in an on-site inspection.